2013
DOI: 10.1590/s1415-98482013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos retornos à escolaridade para trabalhadores do sexo masculino no Brasil

Abstract: Talles Girardi de Mendonça eRESUMO: Este artigo avalia os retornos a anos adicionais de estudos para trabalhadores do sexo masculino no Brasil. Com base nos dados da Pesquisa Nacional por Amostra de Domicílios (PNAD), de 2009, e aplicando-se o procedimento de Heckman, mensuram-se as diferenças nos retornos salariais à escolaridade nos meios urbano e rural. Como aspecto de destaque metodológico e contribuição para o conjunto de estudos sobre retornos à escolaridade, tem-se a incorporação das informações do plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This stems from the fact that the tourism industry remains predominantly male (67% of all workers are of that gender, according to Table 1). An increase in worker age also raises the probability of being employed in the paid labour market, in keeping with the study of Pereira, Lima, Lima, Braga, and Mendonça (2013), which also found that greater ages are linked to an initial trend of an increased likelihood of an individual being occupied up until a certain age, at which this probability reaches its maximal point. From that point onwards, ageing results in the reduction of the probability of being employed in the paid labour market.…”
Section: Resultssupporting
confidence: 82%
“…This stems from the fact that the tourism industry remains predominantly male (67% of all workers are of that gender, according to Table 1). An increase in worker age also raises the probability of being employed in the paid labour market, in keeping with the study of Pereira, Lima, Lima, Braga, and Mendonça (2013), which also found that greater ages are linked to an initial trend of an increased likelihood of an individual being occupied up until a certain age, at which this probability reaches its maximal point. From that point onwards, ageing results in the reduction of the probability of being employed in the paid labour market.…”
Section: Resultssupporting
confidence: 82%
“…Beginning with the analysis of the participation equation, we observe that any increase in working age increases the probability of participating in the paid labour market, with an increase in schooling levels returning a positive marginal effect. According to Pereira, Lima, Lima, Braga, and Mendonça (2013), with the advance of age, there is an initial trend of increasing probability that the individual is employed through to an age when this probability peaks. From that point onwards, ageing begins to drive a reduction in the probability of being active in the labour market.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%